A cross-sectional study on knowledge, attitude, and practices towards exclusive breastfeeding among postnatal mothers at Eastern Division Health Center III in Soroti City. - Niwandinda, Jacken; Okellom, Florence Atino (Student’s Journal of Health Research Africa, 2025)
Background. Exclusive Breastfeeding is one of the practices that can minimize malnutrition in children below 6 months of life. However, undernutrition cases have alarmingly risen from 10% to 19% over the past three years. This study assessed the knowledge, attitudes, and practices toward exclusive breastfeeding among postnatal mothers at Eastern Division Health Center III, Soroti City. Methodology. A descriptive cross-sectional study design was carried out among 30 randomly selected postnatal mothers using a simple random procedure. Data was collected through face-to-face interviews using a pretested semi-structured questionnaire. Data was analyzed and presented in tables, graphs, and pie charts using Excel, from which statements were made. Results. 15/30 (50%) of the respondents were mothers aged between 19 and 35 years, and 11/30 (36.7%) of the respondents had completed secondary education. (46%) Knew the meaning of Exclusive Breastfeeding (40%), knew that EBF was beneficial for infant growth (46.7%), and attended antenatal care (46.7%). (43.3%) Of the respondents who agreed that complementary breastfeeding is good for babies before 6 months, 50% agreed that EBF makes their breasts flat, and 43.3% disagreed that EBF is enough for infant growth in the first 6 months. Low EBF practices were noted as the majority, 60% of the respondents, who complemented breastfeeding their babies. Conclusion. Respondents had average knowledge, though attitudes and practices on exclusive breastfeeding were low. Thus, it is important to provide prenatal education to mothers and fathers on breastfeeding. Recommendation Post-natal mothers at Eastern Division Health Centre III should actively participate in postnatal activities to enhance and promote exclusive breastfeeding practices.